Nanoscale 2CL-20·HMX high explosive cocrystal synthesized by bead milling1. Issue 22 (14th June 2015) - Qiu, Hongwei; Patel, Rajen B.; Damavarapu, Reddy S.; Stepanov, Victor
<x xml:space="preserve">Abstract</x> Nanoscale cocrystal of CL-20 and HMX with a rounded morphology was prepared by bead milling an aqueous suspension of the coformers.